Basal levels of (p)ppGpp differentially affect the pathogenesis of infective endocarditis in Enterococcus faecalis - Colomer-Winter, Cristina (Microbiology Society, 2018)

(untitled) (Microbiology (Reading))
The alarmone (p)ppGpp mediates the stringent response and has a recognized role in bacterial virulence. We previously reported a stringent response-like state in Enterococcus faecalis isolated from a rabbit foreign body abscess model and showed that E. faecalis mutants with varying levels of cellular (p)ppGpp [Δrel, ΔrelQ and the (p)ppGpp(0) ΔrelΔrelQ] had differential abilities to persist within abscesses. In this study, we investigated whether (p)ppGpp contributes to the pathogenesis of E. faecalis infective endocarditis (IE), a biofilm infection of the heart valves. While the stringent response was not activated in heart valve-associated E. faecalis, deletion of the gene encoding the bifunctional (p)ppGpp synthetase/hydrolase Rel significantly impaired valve colonization. These results indicate that the presence of (p)ppGpp is dispensable for E. faecalis to cause IE, whereas the ability to regulate (p)ppGpp levels is critical for valve colonization. Next, we characterized how basal (p)ppGpp levels affect processes associated with IE pathogenesis. Despite being defective in binding to BSA-coated polystyrene surfaces, the Δrel strain bound to collagen- and fibronectin-coated surfaces and ex vivo porcine heart valves as well as the parent and ΔrelΔrelQ strains, ruling out the possibility that the impaired IE phenotype was due to an attachment defect. Moreover, differences in cellular (p)ppGpp levels did not affect extracellular gelatinase activity but significantly impaired enterococcal invasion of human coronary artery endothelial cells. Taken together, this study uncovers for the first time the fact that differences in basal (p)ppGpp levels, rather than the stringent response, differentially affect processes that contribute to the pathogenesis of IE.